Aggregating the news : secondhand knowledge and the erosion of journalistic authority - Coddington, Mark (Mark Allen) (Columbia University Press, 2019)
"Amid the torrent of information we receive every day, aggregation of previously reported stories allows readers to streamline, summarize, and process the news. While aggregation in one form or another has been part of journalism since the nineteenth century, it has taken on a new prominence and influence in today's media ecosystem. While aggregation practices are increasingly being adopted by new digital entities and leading news organizations via news apps, e-mail newsletters, and other formats, they are denigrated by journalists as not "real" journalism and inferior to reporting. More recently, aggregation has been viewed with suspicion as a practice that allows for the news to be repackaged in ways that reflect political bias. Despite the tendency of some aggregators to distort the news, whether for the purpose of clicks or politics, aggregation, Coddington argues, serve an important purpose in the contemporary news environment. Given that aggregation is likely here to stay, journalists and readers need to develop practices to better understand and improve its implementation and influence. Coddington's work is based on his fieldwork and interviews with aggregators at five different news organizations, including both startups and legacy media organizations that use aggregation. The book focuses on how aggregators make decisions on what to publish, how they create narrative, how they understand their audiences, and how they view their own work"--